Challenging surgical management of a giant inguinoscrotal hernia: Report of a case - Vasiliadis, Konstantinos; Knaebel, Hanns-Peter; Djakovic, Nenad; Nyarangi-Dix, Joanne; Schmidt, Jan; Büchler, Markus W. (Surgery today, 2010)
This report describes the surgical management of a giant inguinoscrotal hernia, which extended below the patient’s knees, causing considerable physical discomfort and impairment of his quality of life. Initial management involved improving the patient’s general condition and performing progressive preoperative pneumoperitoneum over 18 days. Surgery involved debulking the contents of the massive hernia sac by performing right hemicolectomy and transverse colectomy, repositioning of the small bowel into the abdominal cavity, resection of the giant hernia sac, and plastic reconstruction of the penis and scrotal region. The abdominal wall was reinforced with composite mesh. Despite a complicated postoperative course, the patient recovered well and has progressively returned to normal activities. Although challenging and demanding, surgery represents the only mode of treatment that can offer the patient with a giant inguinoscrotal hernia a satisfactory level of function and quality of life.